Retrospective Analysis of Antibiotic Resistance Patterns of Uropathogenic Escherichia coli With Focus on Extended‐Spectrum β‐Lactamase at a Tertiary Central Hospital in Saudi Arabia - Khalid M. Alameer; Bandar M. Abuageelah; Rena H. Alharbi; Mona H. Alfaifi; Eman Hurissi; Moayad Haddad; Nabil Dhayhi; Abdulelah S. Jafar; Mousa Mobarki; Hassan Awashi; Shaqraa Musawi; Abdulaziz M. Alameer; et al. (Health Science Reports)
ABSTRACT Background and Aims Urinary tract infections (UTIs) are a prevalent bacterial infection that has substantial implications for healthcare on a global scale. Escherichia coli (E. coli) is a gram‐negative rod responsible for most UTI cases. ESBL‐producing E. coli is widely recognized as a significant contributor to antibiotic resistance. This study aims to evaluate the prevalence and antibiotic resistance trends of ESBL‐producing E. coli in patients with UTIs at a tertiary hospital in Jazan, Saudi Arabia. Methods A retrospective cross‐sectional analysis was conducted on 347 urine specimens collected between January 2022 and March 2023. Results The study found that 31% of E. coli specimens were positive for ESBL. Among patients with ESBL‐producing E. coli, 78.9% were females, and the majority of ESBL‐producing E. coli cases were observed in the outpatient clinic departments. Among all E. coli isolates, ampicillin exhibited the highest resistance rate at 69.3%, aztreonam at 66.7%, and colistin at the lowest resistance. ESBL‐producing E. coli strains exhibited higher resistance rates than non‐ESBL‐producing E. coli strains. Conclusion The study agrees with others in the region and shows a higher prevalence of ESBL‐producing E. coli in the region, emphasizing the importance of antibiotic stewardship programs and infection control measures to mitigate the prevalence and spread of ESBL‐producing E. coli in our region.